2020
DOI: 10.1007/978-3-030-58858-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Agile Team Work Quality

Abstract: The maturity of organizations is measured with process assessment models like the ISO/IEC 33001. The product quality is aligned with internal and external product quality charactersitics based on models like the ISO/IEC 25010. With the shift from the Tailorism-driven process orientation to a more people centric organization, the two dimensions process and product quality have to be extened by the people or team quality dimension. The presented approach offers aspects for agile Team Work Quality (aTWQ), as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…Agility changes how organizations hire, develop and manage their people and how they create and encourage a culture of HR innovation. Recent research has shown that agile procedures enable people to evolve through challenging work, influential partnership, constant reflection, continuous feedback and improvement, all deeply embedded within the workflow (Julian et al , 2019; López-Alcarria et al , 2019; Poth et al , 2020). Denning (2010) also explained that human resource agility (HRA) allows organizations to successfully adapt to unpredictable and rapidly changing disruptive environments.…”
Section: Introductionmentioning
confidence: 99%
“…Agility changes how organizations hire, develop and manage their people and how they create and encourage a culture of HR innovation. Recent research has shown that agile procedures enable people to evolve through challenging work, influential partnership, constant reflection, continuous feedback and improvement, all deeply embedded within the workflow (Julian et al , 2019; López-Alcarria et al , 2019; Poth et al , 2020). Denning (2010) also explained that human resource agility (HRA) allows organizations to successfully adapt to unpredictable and rapidly changing disruptive environments.…”
Section: Introductionmentioning
confidence: 99%
“…Empowered teams can build and improve their delivery procedures and processes independently for fast and innovative solutions. The enabling building block for systematic team empowerment is aTWQ (agile Team Work Quality) as introduced in [17].…”
Section: The Architecture and Characteristics Of Efismentioning
confidence: 99%
“…A highly matured team can master their products and services and work autonomously. To make team maturity transparent and help improve it, the aTWQ approach [17] is part of the empowerment pillar of the EFIS framework.…”
Section: Leveraging Compliance Governance With Efismentioning
confidence: 99%
“…We address team quality aspects with agile Team Work Quality (aTWQ) [43]. As presented in Table I, the SSK guides with questions about the indicators of behavior and interactions between individuals.…”
Section: Team Qualitymentioning
confidence: 99%